In vitro regeneration in cole crops - Shahid, Sonia B; Khan, SZ; Hassan, L (Journal of the Bangladesh Agricultural University, 2011)
The experiment was conducted to optimize a suitable protocol for in vitro regeneration in cole crops. Callus initiation was excellent in the variety Early Tropical. Highest percentage of callus proliferation was observed in Early Tropical (75.0%) followed by Tangail Special Pauslali (55.0%) and the lowest in Tara (40.0% ). Maximum callus proliferation (68.5%) was observed in MS + 3.0 mgL-1 BAP + 0.1 mgL-1 2,4-D + 2.0 mgL-1 AgNO3. Callus proliferation was lowest (40.0%) in MS + 2.5 mgL-1 BAP + 0.1 mgL-1 2,4-D + 2.0 mgL-1 AgNO3. MS medium supplemented with 3.0 mgL-1 BAP + 1.0 mgL-1 2,4-D + 2.0 mgL-1 AgNO3 was the best for shoot initiation & plantlet regeneration. The highest number of shoots per vial was 7.20 and the lowest number of shoots per vial was 4.40. Among the concentration MS + 3.0 mgL-1 BAP + 0.1 mgL-1 2,4-D + 2.0 mgL-1 AgNO3 showed the highest performance of shoots per vial. The variety Tangail Special Pauslali was the best for root initiation. Keywords: Brassica; Cole crops; Callus; In vitro; Regeneration DOI: 10.3329/jbau.v8i2.7930 J. Bangladesh Agril. Univ. 8(2): 227-232, 2010